2022
DOI: 10.1371/journal.pone.0265092
|View full text |Cite
|
Sign up to set email alerts
|

Community health workers experiences and perceptions of working during the COVID-19 pandemic in Lagos, Nigeria—A qualitative study

Abstract: Background Community Health Workers are globally recognised as crucial members of healthcare systems in low and middle-income countries, but their role and experience during COVID-19 is not well-understood. This study aimed to explore factors that influence CHWs’ ability and willingness to work in the COVID-19 pandemic in Lagos. Design A generic qualitative study exploring Community Health Workers experiences and perceptions of working during the COVID-19 pandemic in Lagos, Nigeria. Methods 15 semi-structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…Consistently, we found that higher levels of worry and unprotect perceptions were associated with higher burnout scores over time among frontline HCWs. Participants stated that they were in constant crisis process, working overtime, with multiple changes in their work context, a situation described as insecure and overwhelming [24,36,37]. They also evoked a tendency to adopt a "savior" posture, sacrificing their "basic needs," which could undermine their health at work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, we found that higher levels of worry and unprotect perceptions were associated with higher burnout scores over time among frontline HCWs. Participants stated that they were in constant crisis process, working overtime, with multiple changes in their work context, a situation described as insecure and overwhelming [24,36,37]. They also evoked a tendency to adopt a "savior" posture, sacrificing their "basic needs," which could undermine their health at work.…”
Section: Discussionmentioning
confidence: 99%
“…Stakeholders and mental health professionals are called upon to provide HCWs with interventions to deal with their emerging affective reactions, considering their worries and internal ambivalences. As the pandemic continues, tailored individual and structural interventions should be offered [36], such as group or individual discussion sessions, promoting mutual support among HCWs and counteracting social isolation [37].…”
Section: Discussionmentioning
confidence: 99%
“…For example, CHWs played multiple roles in the 2014 Ebola outbreak in West Africa [11][12][13][14][15]. Most recently, CHWs have been active in the COVID-19 response [16][17][18][19][20][21][22][23]. Research has documented the roles played by CHWs in controlling COVID-19, and the challenges they have experienced [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The need for quality and accessible SRH services further increases in the lockdown period as researchers have documented an increased rate of sexual and gender-based violence (SGBV) in that context [14,15]. Yet, research ndings from Nigeria [16][17][18] and elsewhere [19][20][21][22][23] indicate that COVID-19 and the associated lockdown negatively affected access to SRH services. The reported impact varied considerably by geographies, social and health services contexts, and population settings.…”
mentioning
confidence: 99%
“…Furthermore, while Nigeria is a multi-ethnic country with signi cant regional differences in health-related behaviours and associated factors, studies regarding COVID-19 and healthcare access have been very limited in their geographic focus. Except for the quantitative study by Adelekan and colleagues [16], studies on COVID-19 and access to healthcare in Nigeria have generally been limited to only one of the country's 36 states [17][18].…”
mentioning
confidence: 99%